PHYTOCHEMICALS, VITAMINS,MACRO AND MICRO ELEMENTS AND ANTIMICROBIAL ANALYSIS OF THE STEM BARK OF NAPOLEONA VOGELII(AKPAESU) - Onyrkwere, Eze Sunday; Victoria, Amajoh Chinwe (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Sequel to the increasing application of plant materials in ethnomedicine and for nutritive purposes the phytochemicals, vitamins, macro and micro elements and antimicrobial analysis of the stem bark of Napoleonavogelii were undertaken using standard methods. The result shows that Napoleonavogeliicontains bioactive phytochemicals such as tannin (0.45±0.25%), phytosterols (12.53±0.25%), alkaloids (4.42±0.23%), flavonoids (9.27±0.18%), saponins (4.27±0.25%), hydrogen cyanide (0.37±0.20%). The vitamin analysis shows that the stem bark of Napoleonavogeliicontains vitamin A (1.20±0.03Mg/g), vitamin E (1.31±0.04 Mg/g), vitamin C (2.78±0.04 Mg/g), vitamin B1(7.20±0.05 Mg/g), vitamin B2 (0.90±0.31 Mg/g), vitamin B9(4.09±0.05 Mg/g), vitamin B3(1.27±0.25 Mg/g), vitamin B6(12.50±0.04 Mg/g)andvitaminB12(8.25±0.04Mg/g) in varying amounts while vitaminB5andvitaminB7wereabsent.Sodium(1247mg/kg),Calcium(2006mg/kg),Copper(1.23mg/kg),Phosphorous(410.22mg/kg), Iron(304.660mg/kg), Manganese(56.99mg/kg) and Zinc(2.69mg/kg) were the detectable mineral elements, Potassium (4996mg/kg) had the highest value while Arsenic and Nickel were below detection limit (0.001mg/kg).The result of the antimicrobial screening of the ethanol, butanol and chloroform extracts of the stem bark of Napoleonavogeliiagainst five pathogenic microbes, Escherichia coli, pseudomonas aeruginosa, streptococcus sp, Staphylococcus aureus, and Candida albicans shows that the butanol extract showed higher antimicrobial activities compared to the other extracts. Results from this study have shown that the stem bark of Napoleonavogeliicontains medicinal properties.